2020
DOI: 10.1055/s-0040-1702985
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Tips of Cesarean Section in Case of Breech, Transverse Presentation, and Incarcerated Uterus

Abstract: The presentation, position, and attitude of the fetus should be confirmed by transabdominal ultrasonography on admission and at departure from the ward for cesarean section. It is important to have images of the course of the surgery and delivery of the fetus by confirming the fetal position, location of the placenta and umbilical cord, and volume of amniotic fluid. The operation should be performed by imaging the descent, presentation, position, and attitude of the fetus through external examination according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…However, for patients in whom the diagnosis is delayed beyond week 20, a very high percentage do not receive any type of treatment, potentially leading to the need to end the pregnancy by cesarean section. 15 In some cases, diagnosis is made during the cesarean section, which is associated with, as previously reported in the literature, an increase in maternal-perinatal complications. 7 Globally, this pathology is associated with worse pregnancy outcomes and with higher frequencies of abortion, PROM, and preterm delivery.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, for patients in whom the diagnosis is delayed beyond week 20, a very high percentage do not receive any type of treatment, potentially leading to the need to end the pregnancy by cesarean section. 15 In some cases, diagnosis is made during the cesarean section, which is associated with, as previously reported in the literature, an increase in maternal-perinatal complications. 7 Globally, this pathology is associated with worse pregnancy outcomes and with higher frequencies of abortion, PROM, and preterm delivery.…”
Section: Discussionmentioning
confidence: 93%
“…Our analysis indicates that the early diagnosis of this pathology is associated with higher rates of resolution and with less invasive techniques for treatment. However, for patients in whom the diagnosis is delayed beyond week 20, a very high percentage do not receive any type of treatment, potentially leading to the need to end the pregnancy by cesarean section 15 . In some cases, diagnosis is made during the cesarean section, which is associated with, as previously reported in the literature, an increase in maternal鈥恜erinatal complications 7 …”
Section: Discussionmentioning
confidence: 98%
“…Compared to ultrasound, MRI provides more comprehensive anatomical insights into the pelvis, and has a higher tissue resolution and a wider field of vision. It can not only display the relative positions of the uterus, placenta, and cervix, but can also display the structure of the surrounding pelvic organs, such as the bladder, vagina, and rectum ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…To prevent injuries of enormous stress to the fetus, breech delivery was most suitable. Studies have also suggested, that in cases where an inverted T-incision is not applicable, a vertical incision or a J- shaped incision are other options to consider [ 6 - 7 ]. Inverted T-incisions incidence has increased from 0.2% to 0.9%, with a remaining high risk to maternal health [ 8 ].…”
Section: Discussionmentioning
confidence: 99%